Understanding Proactive Behaviours and Career Success: Evidence From an Emerging Economy - Rasdi, Roziah Mohd; Garavan, Thomas N.; Ismail, Maimunah (Organizations and Markets in Emerging Economies, 2011)
This article explores the relationship between proactive career behaviours and both objective and subjective career success. The study was conducted on a sample of managers within the public sector of an emerging economy (Malaysia). A sample of 288 managers reported on their proactive career behaviours and career success. Results show that managers who engage in individual career management and networking behaviours report more subjective career success. Networking is positively related to both objective and subjective career success. We discuss the implications for managers' career in emerging economies.
Keywords: proactive behaviors; individual career management; networking behavior; computer skills; career success